2016
DOI: 10.1002/2016tc004171
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term fore‐arc basin evolution in response to changing subduction styles in southern Alaska

Abstract: Detrital zircon U-Pb and fission track double-dating and Hf isotopes from the Mesozoic and Cenozoic strata in the southern Alaska fore-arc basin system reveal the effects of two different modes of flat-slab subduction on the evolution of the overriding plate. The southern margin of Alaska has experienced subduction of a spreading-ridge (~62-50 Ma) and an oceanic plateau (~40-0 Ma). When a subducting spreading ridge drives slab flattening, our data suggest that after the ridge has moved along strike retro-arc s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 136 publications
(188 reference statements)
6
30
0
Order By: Relevance
“…The southern Alaska fore-arc basin, in contrast, has experienced a variety of subducting slabs during Cenozoic time, including Paleocene-Eocene subduction of a spreading ridge and Oligocene-Recent subduction of a wedge-shaped oceanic plateau referred to as the Yakutat microplate [Plafker et al, 1994;Haeussler et al, 2003;Ridgway et al, 2012]. Subduction of both these features resulted in flat-slab subduction and previous work has demonstrated that significant upper plate response is recorded in both the sedimentological and provenance record in the fore-arc basin [Finzel et al, 2011[Finzel et al, , 2016Lepain et al, 2013;Kortyna et al, 2014]. Specifically, based on the available data, nonmarine depositional systems have dominated the basin during all of Cenozoic time and sediment has been derived from the retroarc region in addition to the magmatic arc and accretionary prism.…”
Section: Introductionmentioning
confidence: 99%
“…The southern Alaska fore-arc basin, in contrast, has experienced a variety of subducting slabs during Cenozoic time, including Paleocene-Eocene subduction of a spreading ridge and Oligocene-Recent subduction of a wedge-shaped oceanic plateau referred to as the Yakutat microplate [Plafker et al, 1994;Haeussler et al, 2003;Ridgway et al, 2012]. Subduction of both these features resulted in flat-slab subduction and previous work has demonstrated that significant upper plate response is recorded in both the sedimentological and provenance record in the fore-arc basin [Finzel et al, 2011[Finzel et al, , 2016Lepain et al, 2013;Kortyna et al, 2014]. Specifically, based on the available data, nonmarine depositional systems have dominated the basin during all of Cenozoic time and sediment has been derived from the retroarc region in addition to the magmatic arc and accretionary prism.…”
Section: Introductionmentioning
confidence: 99%
“…62-50 Ma), either a spreading ridge that subducted from west to east across the entire southern margin, or a slab break-off event following final suturing of the Insular terranes, resulted in a hiatus in arc magmatism, emplacement of slab-window igneous rocks in the forearc and accretionary prism regions, and high-temperature/low-pressure metamorphism of accretionary prism strata Haeussler et al, 2003;Sisson et al, 2003;Cole et al, 2006;Terhune et al, 2019;Trop et al, 2019). In addition, previous detrital geochronologic and thermochronologic data from the Alaskan forearc basin demonstrate that after this event retro-arc sources become predominant over more proximal arc sources (Finzel et al, 2016).…”
Section: Existing Provenance and Tectonic Modelsmentioning
confidence: 95%
“…The Yakutat microplate is an ∼11-30 km thick, wedge-shaped oceanic plateau that is subducting at a dip angle of 11-16 • , decreasing from west to east, to near the modern coastline (Ferris et al, 2003;Eberhart-Phillips et al, 2006;Worthington et al, 2008Worthington et al, , 2012Christeson et al, 2010;Bauer et al, 2014). Yakutat shallow-subduction-related processes observed in the upper plate in Alaska include changes in (1) the style and location of volcanic arc magmatism, (2) sedimentary basin subsidence and inversion patterns, and (3) sediment sources as a result of accelerated surface uplift above the subducted flat slab (e.g., Enkelmann et al, 2008Enkelmann et al, , 2019Finzel et al, 2011Finzel et al, , 2015Finzel et al, , 2016Trop et al, 2012;Arkle et al, 2013;Finzel and Enkelmann, 2017). Shallow subduction still characterizes the present-day margin of southern Alaska.…”
Section: Existing Provenance and Tectonic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not until well after terminal suturing of the Wrangellia composite terrane to the former continental margin did forearc depocenters start to receive significant continental detritus from inboard terranes. Published studies, for example, show that by Miocene-Pliocene time, interior rivers traversed dissected topography of the Wrangellia composite terrane and delivered abundant sediment eroded from source terranes inboard of the Wrangellia composite terrane, including the Yukon composite terrane (e.g., Bristol et al, 2017;Finzel et al, 2016Finzel et al, , 2015.…”
Section: Implications For Accretion Of the Wrangellia Composite Terranementioning
confidence: 99%